Model Pembelajaran Kontekstual Meningkatkan Hasil Belajar Matematika Siswa Kelas V Sekolah Dasar - Setiawan, Panji; Sudana, I Dewa Nyoman (Jurnal Ilmiah Pendidikan Profesi Guru, 2021)
The low achievement of students’ mathematics learning is due to the lack of students’ understanding of the subject matter presented by the teacher and in the learning process, the teacher has not implemented an innovative learning model. This study aims to analyze the contextual learning model on the mathematics learning outcomes of fifth-grade elementary school students. This research is a classroom action research that consists of two cycles. Each cycle has stages including the action planning stage, the implementation stage, the observation stage, and the reflection stage. In this study, a contextual learning model was used. The subjects of this study were 38 students of class V, consisting of 14 boys and 24 girls. Data collection methods used in this study were observation and multiple-choice tests. Data analysis in this study used qualitative and quantitative descriptive analysis techniques. In the results of the research in the first cycle, there was an increase in students’ mathematics learning outcomes with an average value of 78.42 and a classical mastery percentage of 92%. The results of the research in the second cycle increased to 82.94 with a percentage of 100% classical completeness. This shows that the research target has been achieved in cycle two, namely the average value of student learning outcomes based on the PAP is in the high category. Based on the results of this study, it can be concluded that the use of contextual learning models can improve mathematics learning outcomes for fifth-grade elementary school students.